Innocent in death - Robb, J. D., 1950- (G.P. Putnam's Sons, 2007)
Investigating the baffling murder case of an ordinary and much-loSved private school teacher, New York City lieutenant Eve Dallas struggles to identify who may have wanted the death of an innocent man